2008
DOI: 10.1542/peds.2007-3657
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Exercise Capacity in Children Born Very Preterm

Abstract: In the largest cohort of school-aged children (born very preterm in the 1990s) to undergo extensive lung function and fitness assessments, we demonstrated significant impairment in exercise capacity despite evidence of only mild small-airway obstruction and gas trapping. Additional studies are required to evaluate the cause of this exercise limitation and whether it can be improved with a training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
109
2
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 24 publications
15
109
2
15
Order By: Relevance
“…By contrast, since widespread introduction of antenatal corticosteroids and neonatal surfactant therapy in the early 1990s, BPD is now largely restricted to more immature infants delivered during the early saccular phase and ''new'' BPD has been reported to be characterised by disruption of alveolar development, with reduced alveolar number and enlarged airspaces, but less pulmonary fibrosis and lung injury than previously described [4]. Nevertheless, the degree of persistent airway obstruction, as reflected by spirometry, has remained remarkably constant [2,5,6]. Given that diminished forced expiratory volume in 1 s (FEV1) is a marker of all-cause premature mortality [7] and that those with low LF at initial assessment tend to remain low at subsequent assessments and vice versa [8], there is concern that survivors of preterm birth may be at risk of early onset chronic obstructive pulmonary disease in adulthood [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, since widespread introduction of antenatal corticosteroids and neonatal surfactant therapy in the early 1990s, BPD is now largely restricted to more immature infants delivered during the early saccular phase and ''new'' BPD has been reported to be characterised by disruption of alveolar development, with reduced alveolar number and enlarged airspaces, but less pulmonary fibrosis and lung injury than previously described [4]. Nevertheless, the degree of persistent airway obstruction, as reflected by spirometry, has remained remarkably constant [2,5,6]. Given that diminished forced expiratory volume in 1 s (FEV1) is a marker of all-cause premature mortality [7] and that those with low LF at initial assessment tend to remain low at subsequent assessments and vice versa [8], there is concern that survivors of preterm birth may be at risk of early onset chronic obstructive pulmonary disease in adulthood [3].…”
mentioning
confidence: 99%
“…Although a wide range of tests have been used to assess cardio-respiratory function in survivors of pre-term birth [2,5,6,9,10], relatively few studies have included the full spectrum of available techniques and spirometric parameters remain the most common outcomes, as used during recent school assessments of survivors of the EPICure cohort at 11 yrs of age [11]. In that study, 56% of children born before 25w +6 gestation were found to have abnormal baseline spirometry, 27% had a positive bronchodilator response and 25% a diagnosis of asthma (twice that observed in classmates).…”
mentioning
confidence: 99%
“…Os estudos que envolvem programação fetal com humanos geralmente associam a carência nutricional como estímulo indutor de programação 37,41 . Recentemente tem sido estudadas as consequências do baixo peso ao nascer sobre o nível de aptidão física relacionada à saúde 35,42,43 .…”
Section: Estado Nutricional Atualunclassified
“…Com relação à aptidão cardiorrespiratória, Smith et al 43 mostraram por meio de testes de função pulmonar, como a espirometria, e de aptidão física, como a caminhada de 6 minutos, que a capacidade aeróbia de crianças de 10 anos de idade que nasceram com muito baixo peso é a metade da de crianças nascidas com peso normal. Esses resultados podem ser explicados pelas possíveis disfunções pulmonares em crianças nascidas com muito baixo peso 42,43 , com redução do consumo de oxigênio 35 .…”
Section: Estado Nutricional Atualunclassified
See 1 more Smart Citation